"It’s More Like What You Think of Land": Bringing Together Community and Education Through Mapping (LEARNing Landscapes, 2016)
Community mapping projects involve citizens in the creation of maps that communicate local knowledge, relationships, and visions. The power in community mapping emerges from the process of creating the maps themselves. By exchanging and re ecting upon ideas, stories, and understandings of place, mapmakers develop and strengthen their connections to their communities. This paper explores grade four students’ experience of a community mapping project as it shares the stories and understandings of four participating students. Their narratives illustrate how community mapping can inform students’ understanding of their community, foster and strengthen their community connections, and in uence their perceived place within their community.
Keywords: community; education; knowledge; community mapping; connection